Searching for the one(s): Using Probiotics as Anthelmintic Treatments - Saracino, Maria Priscila; Vila, Cecilia Celeste; Baldi, Pablo César; González Maglio, Daniel Horacio (Frontiers in Pharmacology, 2021)
Helminths are a major health concern as over one billion people are infected worldwide and, despite the multiple efforts made, there is still no effective human vaccine against them. The most important drugs used nowadays to control helminth infections belong to the benzimidazoles, imidazothiazoles (levamisole) and macrocyclic lactones (avermectins and milbemycins) families. However, in the last 20 years, many publications have revealed increasing anthelmintic resistance in livestock which is both an economical and a potential health problem, even though very few have reported similar findings in human populations. To deal with this worrying limitation of anthelmintic drugs, alternative treatments based on plant extracts or probiotics have been developed. Probiotics are defined by the Food and Agriculture Organization as live microorganisms, which, when consumed in adequate amounts, confer a health benefit to the host. It has been proven that probiotic microbes have the ability to exert an immunomodulatory effect both at the mucosa and the systemic level. The immune response against gastrointestinal helminths is characterized as a type 2 response, with high IgE levels, increased numbers and/or activity of Th2 cells, type 2 innate lymphoid cells, eosinophils, basophils, mast cells, and alternatively activated macrophages. The oral administration of probiotics may contribute to controlling gastrointestinal helminth infections since it has been demonstrated that these microorganisms stimulate dendritic cells to elicit a type 2 or regulatory immune response, among other effects on the host immune system. Here we review the current knowledge about the use of probiotic bacteria as anthelmintic therapy or as a complement to traditional anthelmintic treatments. Considering all research papers reviewed, we may conclude that that the effect generated by probiotics on helminth infection depends not only on the parasite species, their stage and localization but also on the administration scheme.